Exploring the Interplay between Digital Phobias and Blended Learning Effectiveness among Secondary School Teachers - Oredein, Afolakemi O.; Ayanshina , Mobolaji T. (Newinera Publisher, 2024)
This study examines the correlation between teachers' digital phobia and the effectiveness of blended learning in Ibadan Metropolis, Oyo State, Nigeria. Through a multistage sampling process involving 186 teachers from private and public secondary schools, the research sheds light on various aspects. It highlights a predominance of female teachers, with public schools hosting a majority of educators. Notably, social media tools like WhatsApp are extensively used for instructional purposes in public schools. The study observes instances of public-school teachers teaching multiple subjects, contrary to specialization policies. Blended learning approaches, particularly the Generic model, are favored, with digital phobias such as Loremophobia and Nomophobia being prevalent. Analysis reveals a strong positive correlation between digital phobia and blended learning effectiveness, emphasizing the importance of teacher commitment in overcoming technological anxieties. Private schools demonstrate superior performance in blended learning effectiveness, potentially due to better access to technology and training. However, private school educators’ exhibit heightened digital phobias, possibly driven by increased expectations and job insecurity. In conclusion, the study underscores the intricate relationship between digital phobias and the efficacy of blended learning among secondary school educators, emphasizing the pivotal role of teachers in leveraging technology for enhanced learning outcomes.